The concrete-representational-abstract sequence of instruction in mathematics classrooms - Mudaly, Vimolan; Naidoo, Jayaluxmi (Faculty of Education, University of the Free State, 2015)
The purpose of this paper is to explore how master mathematics teachers use the concrete-representational-abstract (CRA) sequence of instruction in mathematics classrooms. Data was collected from a convenience sample of six master teachers by observations, video recordings of their teaching, and semi-structured interviews. Data collection also included focus-group interviews with learners. In South Africa, master teachers are considered expert teachers in their discipline. The master teachers in this study were selected by the Department of Education based on their many years of teaching experience; in addition, these selected master teachers taught at six different Dinaledi schools in KwaZulu-Natal (South Africa). A key finding of this research demonstrated that the use of the CRA instructional sequence was paramount for the effective teaching of mathematics. This instructional sequence was found to be predetermined as well as intuitive. The CRA instruction may be used in classrooms where learners are not streamed into ability levels, as is the case with the majority of schools in South Africa. These findings are important for shaping both teacher and curriculum development.
Keywords: Visualisation; Representations; Activity theory; CRA sequence